The Strategic Manipulation of Transnational Temporalities. Issue 3 (3rd May 2016) - Porter, Tony; Stockdale, Liam
Abstract: While it is now widely recognized that globalization is socially constructed, time is often still seen as a natural unalterable force. Drawing on the literature on the social construction of time, we explore the role of human agency in the interaction of time and globalization by developing the concept of temporal systems. These systems are assemblages that bring together temporal artefacts such as clocks and schedules, the temporalities of the natural world and the body, and social practices involving agency, power, and organization. We then explore, through four illustrative examples, how such systems interact with and constitute globalization. These examples are: the initial emergence and contemporary operation of world standard time; the manipulation of the future and speed in global financial markets; the rise of informal international organizations in global governance; and the role of temporality in the strategic behaviour of multinational corporations.